Persistent organochlorine pesticide residues in cocoa beans from Ghana, a concern for public health - Okoffo, E.D; Fosu-Mensah, B.Y.; Gordon, C. (Springer Open - Environmental Systems Research, 2016)
Background: Residual levels of fifteen (15) organochlorine pesticides were determined in 32 cocoa bean samples collected from sixteen (16) selected cocoa farms in the Dormaa West District of Ghana to assess the levels of pesticides contamination. Results: The results show that all cocoa bean samples analysed from the study area had one or more organochlorine pesticide residues detected in them. The study revealed the presence of eight organochlorine pesticide residues in the cocoa bean samples analysed at varying concentrations. The organochlorine pesticide residues detected were aldrin (0.02–0.03 mg/kg), dieldrin (0.02–0.04 mg/kg), lindane (0.03–0.05 mg/kg), beta-HCH (0.02–0.03 mg/kg), p,p'-DDE (0.02–0.03 mg/kg), p,p'-DDD (0.02–0.04 mg/kg), p,p’-DDT (0.04–0.05 mg/kg) and methoxychlor (0.02–0.04 mg/kg). The most frequently found and abundant pesticide residue was the metabolite of DDT (p,p’-DDT) which occurred in 62.5 % of the samples, followed by lindane (56.3 %) and then beta-HCH and p,p’-DDD occurring in 50 % of the samples. None of the detected pesticide mean residues recorded from the various study sites exceeded their European Union (EU) Maximum Residue Limits (MRLs) for cocoa beans except beta-HCH at Krakrom (S3). Conclusion: The levels of organochlorine pesticide residues in the fermented dried cocoa beans analysed compared to the European Union (EU) commission regulations on pesticide residues showed no health risks to consumers of cocoa beans from Ghana and no threat to cocoa export to Europe. The occurrence of organochlorine pesticide residues in the samples analysed could be due to their illegal use by farmers in the study area or due to their past use, since these chemicals are prohibited from agricultural use in Ghana. There should be regular monitoring of pesticide residues especially in cocoa beans to protect consumers from health related risks. There is a need to check and enforce regulations on the use of banned/restricted and unapproved pesticides in cocoa production in Ghana.
Article
Keywords: Cocoa beans; Pesticide residues; Organochlorine; Health risks; Environment